Assessment of microvessel density and carbonic anhydrase-9 (CA-9) expression in rectal cancer. - Rasheed, S; Harris, A; Tekkis, P; Turley, H; Silver, A; McDonald, P; Talbot, I; Glynne-Jones, R; Northover, J; Guenther, T (2009)
AIM: The mechanism by which neoplasias respond to hypoxia determines their biological behavior and prognosis. Understanding the biology of tumors under hypoxic conditions is crucial for the development of anti-angiogenic therapy. Using the largest cohort of rectal adenocarcinomas to date, this study aimed to assess microvessel density (MVD) and carbonic anhydrase-9 (CA-9) expression and to correlate the results with recurrence and cancer-specific survival. MATERIALS AND METHODS: Patients (n=101) who underwent surgery for rectal adenocarcinoma without previous neoadjuvant therapy or metastatic disease were selected. MVD and CA-9 expression were assessed immunohistologically by using the CD34 antibody and the MN/CA9 M75 antibody, respectively. In a multifactorial analysis, the results were correlated with tumor stage, recurrence rate, and long-term survival. RESULTS: MVD was higher with increased T- and N-stages (p<0.01) and associated positively with poor survival (hazard ratio (HR) 1.3 per 10 vessel increase, p<0.01). CA-9 was expressed in 73% of cancers. Negative lymph node status correlated with CA-9 positivity (p<0.05), reflected in a higher rate of CA-9 positivity in earlier Dukes' stages (p<0.05). CA-9 positivity across tumor node metastasis (TNM) stages approached significance (Stage I/II: 80% CA-9 positive vs. 20% CA-9 negative; Stage III: 63% CA-9 positive vs. 37% negative, p=0.051). A trend was seen towards better cancer-specific survival in patients with CA-9 positive carcinomas (HR 0.51, p=0.07) on univariate analysis. DISCUSSION: MVD was higher in more advanced T- and N-stages and may be used as a determinant of survival in patients with rectal adenocarcinomas. CA-9 expression was seen more often in earlier Dukes' stages, possibly representing an early tumor hypoxic response. CA-9 expression by adenocarcinoma cells may confer long-term survival advantage in surgically treated rectal cancer.